2018
DOI: 10.1093/qjmed/hcy054
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic hematuria is a risk factor of incident chronic kidney disease in the Korean general population: a community-based prospective cohort study

Abstract: The presence of MH is associated with an increased risk of incident CKD in the general population. Therefore, attentive follow-up is warranted in persons with MH for early detection of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Our finding that decreased renal function at diagnosis is associated with poor outcome in patients diagnosed with IgAN is consistent with the results of previous studies [26,31]. CHP has also been identified as a risk factor for CKD progression in the general population [32,33]. In a long-term longitudinal study that targeted the general population of Korea (n = 8719), Kim et al [32] reported that subjects with microscopic hematuria with proteinuria (n = 19) had a higher risk of CKD stage 3-5 than those who did not present with these clinical signs (Hazard Ratio 5.4, 95% CI 2.54-11.49, p < 0.001) during a median follow-up of 11.7 years.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding that decreased renal function at diagnosis is associated with poor outcome in patients diagnosed with IgAN is consistent with the results of previous studies [26,31]. CHP has also been identified as a risk factor for CKD progression in the general population [32,33]. In a long-term longitudinal study that targeted the general population of Korea (n = 8719), Kim et al [32] reported that subjects with microscopic hematuria with proteinuria (n = 19) had a higher risk of CKD stage 3-5 than those who did not present with these clinical signs (Hazard Ratio 5.4, 95% CI 2.54-11.49, p < 0.001) during a median follow-up of 11.7 years.…”
Section: Discussionsupporting
confidence: 92%
“…CHP has also been identified as a risk factor for CKD progression in the general population [32,33]. In a long-term longitudinal study that targeted the general population of Korea (n = 8719), Kim et al [32] reported that subjects with microscopic hematuria with proteinuria (n = 19) had a higher risk of CKD stage 3-5 than those who did not present with these clinical signs (Hazard Ratio 5.4, 95% CI 2.54-11.49, p < 0.001) during a median follow-up of 11.7 years. Moreover, in a Japanese study of adult patients with AUA initially identified as a result of mass urine screening (n = 772), a high proportion (23%) of individuals with CHP (n = 155) also presented with deterioration of renal function (serum creatinine > 2.0 mg/dL) during a median follow-up period of 6.3 years [33].Very recently, Shima et al [34] reported that, among 25 children diagnosed with crescentic IgAN, 16 children (64%) were initially diagnosed with IgAN by SUS and most of them (14 of 16) presented with CHP.…”
Section: Discussionmentioning
confidence: 99%
“…A large nationwide population-based study examined the long-term risk of end-stage kidney disease (ESKDearlier denoted ESRD) among Israeli adolescents and persistent asymptomatic isolated microscopic hematuria was associated with an 18-fold increased ESKD risk [5]. Similar results, though less evident, have been reported by three smaller cohort studies conducted on East Asian populations evaluating long-term risk of chronic kidney disease (CKD), ESKD or kidney function deterioration among patients with microscopic hematuria [6][7][8]. All previous studies however, investigated selected subpopulations using volunteer recruitment and most of them were limited by small sample sizes and loss to follow-up.…”
Section: Introductionmentioning
confidence: 73%
“…Yet, hematuria has been associated with increased risk of kidney disease in individuals where initial work-up revealed no apparent underlying cause of an abnormal dipstick finding [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, regardless of its origin, hematuria has been reported to influence patient outcomes and renal function in the general population. Hematuria is associated with the incidence of acute kidney injury (AKI) [ 2 ] and chronic kidney disease (CKD) [ 3 ]. Moreover, a long-term follow-up study revealed that persistent asymptomatic hematuria correlated with increased risk of renal progression [ 4 ].…”
Section: Introductionmentioning
confidence: 99%